Characteristics of Turkish children with Type 2 diabetes at onset: a multicentre, cross-sectional study - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP (WILEY, 2019)
Aims To describe the baseline clinical and laboratory findings and treatment modalities of 367 children and adolescents diagnosed with Type 2 diabetes in various paediatric endocrinology centres in Turkey. Methods A standard questionnaire regarding clinical and laboratory characteristics at onset was uploaded to an online national database system. Data for 367 children (aged 6-18 years) newly diagnosed with Type 2 diabetes at 37 different paediatric endocrinology centres were analysed. Results After exclusion of the children with a BMI Z-score < 1 SD, those with genetic syndromes associated with Type 2 diabetes, and those whose C-peptide and/or insulin levels were not available, 227 cases were included in the study. Mean age was 13.8 +/- 2.2 (range 6.5-17.8) years, with female preponderance (68%). Family history of Type 2 diabetes was positive in 86% of the children. The mean BMI was 31.3 +/- 6.5 kg/m(2) (range 18.7-61) and BMI Z-score was 2.4 +/- 0.8 (range 1-5). More than half (57%) of the children were identified by an opportunistic diabetes screening due to existing risk markers without typical symptoms of diabetes. Only 13% (n = 29) were treated solely by lifestyle modification, while 40.5% (n = 92) were treated with metformin, 13% (n = 30) were treated with insulin, and 33.5% (n = 76) were treated with a combination of insulin and metformin initially. Mean HbA(1C) levels of the insulin and combination of insulin and metformin groups were 98 (11.1%) and 102 mmol/mol (11.5%), respectively, and also were significantly higher than the lifestyle modification only and metformin groups mean HbA(1C) levels (70(8.6%) and 67 mmol/mol (8.3%), respectively). Conclusions An opportunistic screening of children who are at high risk of Type 2 diabetes is essential, as our data showed that > 50% of the children were asymptomatic at diagnosis. The other important result of our study was the high rate of exclusion from the initial registration (38%), suggesting that accurate diagnosis of Type 2 diabetes in youth is still problematic, even for paediatric endocrinologists.
Keywords: YOUTH; MELLITUS; ADOLESCENTS; OBESITY; TRENDS